Acclimatization influence on the formation of the maral, Cervus elaphus Linnaeus, 1758 parasites fauna in the Northern Tien Shan, Kazakhstan - Оmarkhan Berkinbay; Maratbek Suleimenov; Bayzhan Omarov; Almas Tuganbay; Maxat Berdikulov; Yerkegali Baimukhanbetov; Gulmira Utebayeva (Caspian Journal of Environmental Sciences)
Analysis of the literature and own research have shown that 53 species of parasites are parasitized in marals living in Kazakhstan: 6 species of protozoa, 3 trematodes, 5 cestodes, 36 nematodes and 3 ectoparasites; in Altai marals  50 species including 6 protozoa, 3 trematodes, 5 cestodes, 34 nematodes and 3 ectoparasites; in Alatau marals 15 species including  4 protozoa, 2 trematodes, 2 cestodes, 6 nematodes and 3 ectoparasites; in North Tien Shan marals  7 species including 1 trematode, 1 cestode, and 5 nematodes. During acclimatization, marals lost 25 species of helminths (Acanthospiculum cervipedis, A. flexuosa, Ashworthius sidemi, A. gagarini, Bicaulus sagittatus, B. tuvae, Dictyocaulus eckarti, Elaphostrongylus cervi, Nematodirus oiratianus, Oesophagostomum radiatum, Ostertagia gruhneri, O. ostertagi, O. antipini, Ostertagiella circumcincta, Schulzinema miroljubovi, Skrjabinema ovis, Chavertia ovina, Spiculopteragia schulzi, S. spiculoptera, Trichocephalus capreoli, T. ovis, Trichostrongylus axei, T. colubriformis, Spiculopteragia asymmetrica and Strongyloides papillosus) and acquired 2 species of helminths (Bunostomum phlebotomum and Haemonchus contortus). Common to all marals are 3 species of protozoa (Eimeria cervi, E. gallivalerioi and E. robusta), 4 species of helminths (Paramphistomum cervi, Capillaria bovis, Nematodirus spathiger and Trichocephalus skrjabini) and 3 species of ectoparasites (Lipoptena cervi, Hypoderma diana and Booponus borealis). Five species of helminths are common to marals of Altai and Northern-Tien Shan. Acclimatizers can be involved in the circulation of these helminths. Since they are familiar with these parasites at native land and in a new habitat.